Ostreococcus tauri is a new model green alga for studying iron metabolism in eukaryotic phytoplankton. (December 2016) - Lelandais, Gaëlle; Scheiber, Ivo; Paz-Yepes, Javier; Lozano, Jean-Claude; Botebol, Hugo; Pilátová, Jana; Žárský, Vojtěch; Léger, Thibaut; Blaiseau, Pierre-Louis; Bowler, Chris; Bouget, François-Yves; Camadro, Jean-Michel; et al.
Abstract Background Low iron bioavailability is a common feature of ocean surface water and therefore micro-algae developed original strategies to optimize iron uptake and metabolism. The marine picoeukaryotic green algaOstreococcus tauri is a very good model for studying physiological and genetic aspects of the adaptation of the green algal lineage to the marine environment: it has a very compact genome, is easy to culture in laboratory conditions, and can be genetically manipulated by efficient homologous recombination. In this study, we aimed at characterizing the mechanisms of iron assimilation inO. tauri by combining genetics and physiological tools. Specifically, we wanted to identify and functionally characterize groups of genes displaying tightly orchestrated temporal expression patterns following the exposure of cells to iron deprivation and day/night cycles, and to highlight unique features of iron metabolism inO. tauri, as compared to the freshwater model algaChalamydomonas reinhardtii . Results We used RNA sequencing to investigated the transcriptional responses to iron limitation inO. tauri and found that most of the genes involved in iron uptake and metabolism inO. tauri are regulated by day/night cycles, regardless of iron status.O. tauri lacks the classical components of a reductive iron uptake system, and has no obvious iron regulon. Iron uptake appears to be copper-independent, but is regulated by zinc. Conversely, iron deprivation resulted in the transcriptional activation of numerous genes encoding zinc-containing regulation factors. Iron uptake is likely mediated by a ZIP-family protein (Ot-Irt1) and by a new Fea1-related protein (Ot-Fea1) containing duplicated Fea1 domains. The adaptation of cells to iron limitation involved an iron-sparing response tightly coordinated with diurnal cycles to optimize cell functions and synchronize these functions with the day/night redistribution of iron orchestrated by ferritin, and a stress response based on the induction of thioredoxin-like proteins, of peroxiredoxin and of tesmin-like methallothionein rather than ascorbate. We briefly surveyed the metabolic remodeling resulting from iron deprivation. Conclusions The mechanisms of iron uptake and utilization byO. tauri differ fundamentally from those described inC. reinhardtii . We propose this species as a new model for investigation of iron metabolism in marine microalgae.